Murder by Design - Bloch, Jon P. (St. Martin's Minotaur, 2004)
Opting to have his home remodeled on a popular cable reality show, celebrity gossip columnist Rick Domino is horrified when the consulting designer is found brutally murdered, a case for which Rick teams up with unstylish but attractive police detective Terry Zane.
Keywords: Crimes against; Fiction; Fiction; Hollywood (Los Angeles, Calif.); Fiction; Interior decorators; Fiction; Television programs; Gossip columnists; dept.soc; faculty_collection

Juvenile delinquency - Kenty-Drane, Jessica L. (Men and masculinities: a social, cultural, and historical encyclopedia, 2004)
This reference analyzes, summarizes, and explains the complexities of men's lives and the idea of modern manhood. It looks at literature, art, and music from a gender perspective, and covers intimacy, sexual violence, pornography, sexism and rituals.
Keywords: dept.soc